Muslim self-concept measurement model: towards filling the research gap of self-concept among Muslims - Nurul Asiah Fasehah Muhamad,; Noornajihan Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
A person’s understanding of self is significantly associated with the world view that he or she believes in. This self understanding concept shall only be well established if it is viewed from the perspective that is connected to real epistemology. The importance of this understanding is due to its influence on human perception in all matters related to themselves. As a Muslim with an ultimate goal, which is the happiness of the world and the hereafter, then the real conceptualisation of oneself is essential. However, the influence of secularism and dualism that exist in the education stream is disconcerting in this regard. Therefore, the concept of self in Islam shall be examined and re-assessed. To evaluate the self-concept of a Muslim, the concept and instrument used must be based on the Islamic philosophy and realm. However, the variety of instruments used to evaluate the existing self-concept are in accordance with the Western epistemology, which contradicts the Islamic world view to describe the self-concept of a Muslim. Thus, this study aims to propose an ideal self-concept evaluation model for studies involving Muslims. In conclusion, there are limited studies carried out and leave a decent impact to researchers, especially in the field of Education and Psychology and Humanities.